Diagnosis and management of aorto-left ventricular tunnel - Pallavi Kathare; Rama G Subramanyam; Tapan Kumar Dash; Kalyana Sundaram Muthuswamy; K Raghu; Nageswara Rao Koneti (Wolters Kluwer Medknow Publications, 2015)
Background: Aorto-left ventricular tunnel (ALVT) is a rare congenital extracardiac channel with progressive left ventricular dilatation needs early correction. Materials and Methods: This is a report of diagnosis and management of aorto-left ventricular tunnel (ALVT) over a period of 11 years from a single institution. Seven patients (age range: 7 days-45 years) presented with heart failure. The diagnosis of ALVT was made by transthoracic echocardiogram in all cases. Results: Treatment was refused by two patients who died during follow-up. Surgical closure of the tunnel was done in four cases, of which one needed Bentall procedure. Two patients had residual leak after the surgery. Transcatheter closure using Amplatzer muscular device was performed in two cases (for postoperative residual leak in one and primary procedure in the other). Significant hemolysis developed in one of them, necessitating the removal of the device and closed surgically. This child underwent aortic valve replacement two years later. All the remaining patients were doing well during the median follow-up of 30 months (range: 1.5-9 years). Conclusion: ALVT is a rare and potentially fatal anomaly that is ideally managed surgically. Catheter closure has a limited role.